Carbon-stock estimation in three types of coal post-mining reclamation at East Kutai Regency, East Kalimantan - Fauziah; Fiqa, Abban Putri; Lestari, Dewi Ayu; Budiharta, Sugeng (Jurnal Penelitian Kehutanan Wallacea, 2021)
The success of a reclamation process could be evaluated by calculating the carbon stocks in the area. Carbon stock is an ecosystem service that can be assessed quantitatively. The reclamation process in the coal post-mining area in East Kalimantan needs to be assessed by comparing it to the reference area. The aim of this study was to determine the value of carbon stock in the three types of coal post-mining reclamation areas (Type A: without shade trees, Type B: with one species shade trees, Type C: with more than one species of shade trees), then compared to the natural forest area used as the reference site. The research was carried out by making plots inside the reference site and in the reclamation areas, at the tree, poles, and sapling stages. The results were analyzed descriptively and statistically for each reclamation type refer to the conservation area. The results showed that reclamation type C, with older year plant, had higher carbon stock compared to Type B, or Type A, ie. 51.9 t C/ha, 37.8 t C/ha, and 2.9 t C/ha respectively. However, the carbon stock in the three types of reclamation area is still much lower, than the conservation area which reaches 296.8 t C/ha. Thus, the older and more diverse species planted in a reclamation area plant, the higher carbon stock saved. Moreover, planting shade trees can also help increase the value of carbon stocks in a reclamation area.